2005
DOI: 10.1093/ejo/cji042
|View full text |Cite
|
Sign up to set email alerts
|

Ranking facial attractiveness

Abstract: The first aim of this investigation was to assemble a group of photographs of 30 male and 30 female faces representing a standardized spectrum of facial attractiveness, against which orthognathic treatment outcomes could be compared. The second aim was to investigate the influence of the relationship between ANB differences and anterior lower face height (ALFH) percentages on facial attractiveness. The initial sample comprised standardized photographs of 41 female and 35 male Caucasian subjects. From these, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
2
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 18 publications
5
45
2
5
Order By: Relevance
“…Similarly, in a study by Knight and Keith, 35 increased anterior LFH was found to be associated with less attractive faces for females, but no such trend existed for males. Ioi et al 34 also reported that nonexpert raters rated slightly shorter female profile silhouettes as the most favored.…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, in a study by Knight and Keith, 35 increased anterior LFH was found to be associated with less attractive faces for females, but no such trend existed for males. Ioi et al 34 also reported that nonexpert raters rated slightly shorter female profile silhouettes as the most favored.…”
Section: Discussionmentioning
confidence: 71%
“…Assessment of facial profile changes in patients treated with maxillary premolar extractions original article facial profile preferences for the anteroposterior position of the mandible showed that the preference of orthodontists also differed in relation to both lay groups (Caucasian and Japanese). Disagreements were also observed between orthodontist evaluators in studies of facial attractiveness, 10,11 showing that lay people were less careful in the assessment of this issue. The results of studies 2,3 on the effect of treatment with and without extraction showed that orthodontists demonstrated a more accurate perception of small changes in facial profile.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cephalometric measurements that define facial profiles were found to be poorly correlated with the perception of facial esthetics. [21][22][23] The aims of this study were to evaluate the outcome of orthognathic surgery by objective cephalometric measurement of posttreatment soft-tissue profile and by subjective evaluation of profile esthetics by laypersons and clinicians. Another aim of this study was to investigate the effects of soft-tissue cephalometric variables on assessment of postsurgical profile esthetics by laypersons and professionals.…”
Section: Introductionmentioning
confidence: 99%